Développement du livre Pop-up pour l’apprentissage du français « emploi du temps » pour la compréhension écrite des lycéens - Yolanda Fransiska Aftriningsih; Aisyiah Al Adawiyah (Didacticofrançia: Journal Didactique du FLE (Français Langue Étrangère), 2025)
This study was conducted to determine the feasibility of Pop-Up Books to support reading learning in French, because it was found that the learning support used by teachers was less varied. The purpose of this study is to describe the needs of teachers and students related to the Pop-Up Book “Emploi du Temps” for reading learning and describe the development of the Pop-Up Book. This research is a research and development (R&D). The data collection techniques used were observation and questionnaires. The results of the needs analysis of teachers and students show that teachers and students are interested in 3D Pop-Up Book learning media. The result of this research is a 3D Pop-Up Book learning media product on Emploi du Temps material for reading skills.